Pectic Oligogalacturonide Facilitates the Synthesis and Activation of Adiponectin to Improve Hepatic Lipid Oxidation. Issue 20 (31st August 2021) - Yu, Qianhui; Chen, Xuejiao; Sun, Xiao; Li, Wenjie; Liu, Tianzhi; Zhang, Xiushan; Li, Yuqing; Li, Tuoping; Li, Suhong
Abstract : Scope: Adiponectin (ADPN), a kind of adipokines, plays an important role in the regulation of lipid metabolism. The objective of this study is focused on the ADPN to investigate the functional mechanisms of pectin oligosaccharide (POS) from hawthorn fruit in the improvement of hepatic fatty acid oxidation. Method and Results: High‐fat fed mice are used in this experiment. POS is administrated with the doses of 0.25, 0.75, and 1.5 g kg −1 diet, respectively. The results demonstrate that gene and protein expressions of ADPN synthesis regulators involved in PKA/ERK/CREB and C/EBPα/PPARγ pathways are upregulated by POS administration. POS also activates the AdiopR1/AMPKα/PGC1 and AdipoR2/PPARα signaling pathways to improve the fatty acid oxidation in the liver, which is further accelerated by the enhancement of mitochondrial functions. Conclusion: POS can act as an ADPN activator to improve lipid metabolism, leading it to the applications of biomedical and functional foods for ameliorating chronic liver diseases resulted from a high‐energy diet. Abstract : Pectin oligosaccharide enhances the adiponectin (ADPN) synthesis in adipose tissue. ADPN released from adipocytes improves hepatic fatty acid oxidation.